COVID-19: INTRAPULMONARNI ALKALNI VODONIK-PEROKSID MOŽE ODMAH POVEĆATI KISEONIČNOST KRVI - Urakov, Aleksandr; Fisher, Evgeniy; Svetova, Milena; Suntsova, Darya; Yagudin, Ilnur (Medicinski časopis, 2022)
It has been shown that the new coronavirus infection is life-threatening for patients not because of the COVID-19 virus, but because of the complications it causes. The most dangerous complication of this disease is the airway obstruction syndrome, which occurs with atypical pneumonia. Blockage of the airways occurs due to the accumulation of excessively large amounts of mucus and pus in them and swelling of the lung tissue, so ventilation of the lungs with air becomes almost impossible.  The sad outcome of respiratory obstruction is hypoxia and hypoxic brain damage. Under these conditions, extracorporeal membrane oxygenation remains the only known way to increase blood oxygenation. However, in 2021, it was shown that intra-pulmonary administration of a warm alkaline solution of hydrogen peroxide immediately turns mucus and pus into oxygen foam and increases blood oxygen saturation. The proposed technology is a new variant of emergency blood oxygenation in severe suffocation caused by blockage of the respiratory tract with mucus, pus and blood.
Keywords: mucus; pus; respiratory blockage; hypoxia; mucolytics; oxygen; recanalization